Evaluasi Profil Sensori Abon Ikan Jenis Pelagis Besar Menggunakan Metode Rate-All-That-Apply (RATA) - Inten Kusuma Dewi, Ni Made; Suparthana, I Putu; Pratiwi, I Desak Putu Kartika (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 3 (2021): Jurnal ITEPA, 2021)
This research aims to determine the sensory profile of commercial shredded large pelagic fish based on consumer acceptance and the intensity of sensory attributes that determine consumer preference using the Rate All That Apply (RATA) method. Six shredded products that were used as samples were tested in one sampling session by 65 panelists. This research was designed to create a sensory profile using principal component analysis (PCA) and analysis of variance (ANOVA) followed by the Duncan test, determining consumer preferences using Preference Mapping, and then making target market predictions using least square partial regression. The results showed that all products have similarities based on PCA but have different intensity based on ANOVA. The results of the preference mapping panelist analysis showed that Q products had the highest level of preference with the attributes favored by consumers such as sweet aroma and spices, fibrous and dry texture, and sweet taste.